Forecasting Analysis of Optimal Rice Stock Using The Modeleconomic Order Quantity (EOQ) at Perum BULOG Warehouse GBB Punggaloba, Kendari Barat District, Kendari City - Bilmuminin, Bilmuminin; Sarinah, Sarinah; Indarsyih, Yusna (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This study aimed to analyze the forecasting of the optimal stock of rice using the economic order quantity (EOQ) model at the BULOG Warehouse GBB Punggaloba, West Kendari District, Kendari City. The research used forecasting methods through the Minitab 16 application and economic order quantity (EOQ) analysis. The inventory flow for Bulog warehouses comes from domestic rice procurement (DN). The procurement of DN rice is spread throughout Southeast Sulawesi Province. The results obtained are that in 2022, the rice supply that Perum BULOG Warehouse GBB Punggaloba must carry out is 5,323,696.04 kg, with a total economic order (EOQ) of 80,209.43 kg, an order frequency of 775 times, and a total inventory cost of Rp. 58,278,984,682.54. As for ensuring the stability of rice availability in 2022, Perum BULOG needs to prepare a total safety stock (SS) of 15,971,088.13, with an average of 1,330,924.01 kg/month, a maximum total supply (MI) of 16,051,297.57 kg, with an average of 1,337,608.13 kg/month, and for the continuity of supplies, it is necessary to determine the reorder point (ROP) with a total of 16,326,001.20 kg and an average of 1,360,500.10 kg/ month.